Tuning high frequency magnetic properties and damping of FeGa, FeGaN and FeGaB thin films - Derang Cao (AIP Advances, 2017)
A series of FeGa, FeGaN and FeGaB films with varied oblique angles were deposited by sputtering method on silicon substrates, respectively. The microstructure, soft magnetism, microwave properties, and damping factor for the films were investigated. The FeGa films showed a poor high frequency magnetic property due to the large stress itself. The grain size of FeGa films was reduced by the additional N element, while the structure of FeGa films was changed from the polycrystalline to amorphous phase by the involved B element. As a result, N content can effectively improve the magnetic softness of FeGa film, but their high frequency magnetic properties were still poor both when the N2/Ar flow rate ratio is 2% and 5% during the deposition. The additional B content significantly led to the excellent magnetic softness and the self-biased ferromagnetic resonance frequency of 1.83 GHz for FeGaB film. The dampings of FeGa films were adjusted by the additional N and B contents from 0.218 to 0.139 and 0.023, respectively. The combination of these properties for FeGa films are helpful for the development of magnetostrictive microwave devices.